2021
DOI: 10.1113/ep089553
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy and high salt increase blood pressure and alter sodium transport proteins in peripheral blood mononuclear cells of adult Wistar rats

Abstract: New Findings What is the central question of this study?In a model of salt‐sensitive hypertension in ovariectomized (oVx) adult Wistar rats, what is the expression of proteins related to sodium transport in peripheral blood mononuclear cells (PBMCs), and how does the response of proteins to high sodium intake compare with changes in blood pressure in intact female rats? What is the main finding and its importance?Sodium transport proteins in PBMCs react to high sodium and blood pressure markedly differently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(66 reference statements)
0
1
0
Order By: Relevance
“… 57 A subsequent study demonstrated that female ovariectomized Wistar rats, which are salt-sensitive, exhibited increased NKCC1 expression in peripheral blood mononuclear cells in response to a high-salt diet. 60 Du et al 61 showed an increase in SGK1 in hypertensive mouse spleen and that treating mice with an SGK1 inhibitor significantly reversed cardiac and renal dysfunction.…”
Section: Sgk1mentioning
confidence: 99%
“… 57 A subsequent study demonstrated that female ovariectomized Wistar rats, which are salt-sensitive, exhibited increased NKCC1 expression in peripheral blood mononuclear cells in response to a high-salt diet. 60 Du et al 61 showed an increase in SGK1 in hypertensive mouse spleen and that treating mice with an SGK1 inhibitor significantly reversed cardiac and renal dysfunction.…”
Section: Sgk1mentioning
confidence: 99%